Asthma, rhinitis, and dermatitis in workers exposed to reactive dyes. Issue 1 (January 1993) - Nilsson, R; Nordlinder, R; Wass, U; Meding, B; Belin, L
Abstract : A survey was conducted at 15 textile plants with dyehouses in western Sweden. Employees with a history of work related rhinitis, asthma, or skin symptoms were offered a clinical and immunological investigation including skin prick tests, skin patch tests, and radioallergosorbent tests (RASTs) to detect specific allergy to reactive dyes. Among the 1142 employees, 162 were exposed to reactive dyes and 10 of these (6%) reported work related respiratory or nasal symptoms. An allergy to reactive dyes could be confirmed in five (3%, 95% confidence interval 1-7%). All but one had been exposed to reactive dyes for one year or less before the onset of symptoms. Positive RASTs could be detected in four of the five patients. All of the RAST positive patients were positive to remazol black B, but six out of eight additional remazol dyes also elicited positive results. RAST and RAST inhibition showed a cross reactivity between some of the dyes. Seven persons with work related dermatitis and three with urticaria or Quincke oedema were found. In one patient contact dermatitis to a monoazo dye was shown, but no positive patch test reactions to reactive dyes. IgE-mediated allergy to reactive dyes seems to be an important cause of respiratory and nasal symptoms among dyehouse employees exposed to dust from reactive dyes.